Pericardial and Pleural Effusion in Patient with Relapse Stage IV Breast Cancer: Same Pathology, Different Etiology? - Vienna Rosalinda; Anggoro Budi Hartopo; Dyah Wulan Anggrahini; Bambang Irawan (ACI (Acta Cardiologia Indonesiana), 2018)
Pericardial effusion associated with malignacy has poor prognosis. The prompt identification of etiology is mandatory, such that timely management can be performed and survival can be increased. However, difficulty in etiology determination is commonly encountered. In this case, we report female patient with relapse stage IV breast cancer who develop massive pericardial and bilateral pleural effusion. The similar characteristics were found in both effusion fluids, however the identification of etiology was not similar. Metastatic cells were found in pleural effusion, whereas they were absent in pericardial effusion.